E-WoM Information Influences ESQA Cosmetics Consumer Purchase Intention on TikTok Application - Prabawati, Raden Roro Sekar Maya; Fadhilla, Hanifa Nur (Image : Jurnal Riset Manajemen, 2024)
The increasingly rapid development of technology is directly proportional to global economic growth. This influences the symptoms that continue to increase in online purchases. A lot of buying interest arises from the influence of reviews on social media. Social media is now replacing the role of traditional word-of-mouth and introducing a new phenomenon, namely electronic word-of-mouth (eWOM). TikTok is a social media platform whose development is increasing from year to year with the presence of beauty content in it. ESQA Cosmetics is a local brand that is popular on social media platforms, especially on TikTok. This research aims to determine the influence of eWOM in the TikTok application on purchase interest in ESQA Cosmetics. This research collected data from 270 samples according to criteria via Google Form. PLS-SEM using SmartPLS was chosen in the research to carry out data analysis. This research also have two variable mediator that used to strengthen research. This research found that Information Quality and Information Credibility have a significant positive effect on Information Usefulness. Then the Usefulness of Information has a significant positive effect on Information Adoption. Furthermore, Information Adoption has a significant positive effect on Purchase Intention. This research can be useful for ESQA Cosmetics and other local brands in carrying out their marketing strategies.